Hepatocyte programmed cell death: the trigger for inflammation and fibrosis in metabolic dysfunction-associated steatohepatitis - Cheng, Zilu; Chu, Huikuan; Seki, Ekihiro; Lin, Rong; Yang, Ling (Frontiers in Cell and Developmental Biology, 2024)
By replacing and removing defective or infected cells, programmed cell death (PCD) contributes to homeostasis maintenance and body development, which is ubiquitously present in mammals and can occur at any time. Besides apoptosis, more novel modalities of PCD have been described recently, such as necroptosis, pyroptosis, ferroptosis, and autophagy-dependent cell death. PCD not only regulates multiple physiological processes, but also participates in the pathogenesis of diverse disorders, including metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD is mainly classified into metabolic dysfunction-associated steatotic liver (MASL) and metabolic dysfunction-associated steatohepatitis (MASH), and the latter putatively progresses to cirrhosis and hepatocellular carcinoma. Owing to increased incidence and obscure etiology of MASLDMASH, its management still remains a tremendous challenge. Recently, hepatocyte PCD has been attracted much attention as a potent driver of the pathological progression from MASL to MASH, and some pharmacological agents have been proved to exert their salutary effects on MASLD MASH partly via the regulation of the activity of hepatocyte PCD. The current review recapitulates the pathogenesis of different modalities of PCD, clarifies the mechanisms underlying how metabolic disorders in MASLD induce hepatocyte PCD and how hepatocyte PCD contributes to inflammatory and fibrotic progression of MASH, discusses several signaling pathways in hepatocytes governing the execution of PCD, and summarizes some potential pharmacological agents for MASLD MASH treatment which exert their therapeutic effects partly via the regulation of hepatocyte PCD. These findings indicate that hepatocyte PCD putatively represents a new therapeutic point of intervention for MASHLD.